The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1439-0485.2010.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative reproductive biology of two southwestern Atlantic populations of the hermit crab Pagurus exilis (Crustacea: Anomura: Paguridae)

Abstract: Pagurus exilis (Benedict, 1892) is an endemic South Atlantic hermit crab with a distribution ranging from Rio de Janeiro State, Brazil, to Buenos Aires Province, Argentina. The present study analyzed the reproduction of two populations at the extremes of this geographical distribution, and compared their reproductive period, fecundity, and changes in egg size and egg volume during the incubation period in order to assess the variability over this latitudinal range. Hermit crabs were collected monthly over a 2‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Thus, females of P. armatus in lower latitudes (Pacific Costa Rica) produced substantially more and smaller eggs than those in higher latitudes (Brazil). These findings resemble latitudinal differences in egg production observed in other decapods (Lonsdale and Levinton 1985;Wehrtmann and Kattner 1998;Lardies and Castilla 2001;Lardies and Wehrtmann 2001;Brante et al 2003;Bas et al 2007;Terossi et al 2010b) and are in accordance with the idea that one species can produce a large quantity of small eggs or a lesser quantity of large eggs (Christiansen and Fenchel 1979;Wägele 1987;Giangrande et al 1994). However, this hypothesis is based upon the assumption that in both scenarios the species is investing the same amount of energy in egg production.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, females of P. armatus in lower latitudes (Pacific Costa Rica) produced substantially more and smaller eggs than those in higher latitudes (Brazil). These findings resemble latitudinal differences in egg production observed in other decapods (Lonsdale and Levinton 1985;Wehrtmann and Kattner 1998;Lardies and Castilla 2001;Lardies and Wehrtmann 2001;Brante et al 2003;Bas et al 2007;Terossi et al 2010b) and are in accordance with the idea that one species can produce a large quantity of small eggs or a lesser quantity of large eggs (Christiansen and Fenchel 1979;Wägele 1987;Giangrande et al 1994). However, this hypothesis is based upon the assumption that in both scenarios the species is investing the same amount of energy in egg production.…”
Section: Discussionsupporting
confidence: 76%
“…However, the number of available studies regarding this subject is still limited, which hinders the development of a more complete understanding of the evolution of life-cycle strategies in this highly diverse group of crustaceans (Garcia and Mantelatto 2001). Some studies demonstrated intraspecific differences along latitudinal gradients in the reproductive biology of decapods, including anomuran species (Jones and Simons 1983;Clarke 1987;Wehrtmann and Kattner 1998;Hernáez 2001;Lardies and Wehrtmann 2001;Brante et al 2003;Castilho et al 2007;Terossi et al 2010b). The reasons for the latitudinal cline in reproductive features of marine invertebrates are still under discussion (Clarke 1992(Clarke , 1993Gallardo and Penchaszadeh 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For example, diff erent strategies are adopted by anomuran (Miranda et al, 2006 ;Torati and Mantelatto, 2008 ;Terossi et al, 2010) and caridean (Corey and Reid, 1991 ;Pavanelli et al, 2008 ) populations of the same species in different localities, as well as by diff erent species inhabiting the same area.…”
Section: Discussionmentioning
confidence: 99%
“…1, table 5). This suggests that this species may not present a latitudinal variation of egg production and/or may have experienced similar environmental conditions, especially food availability and temperature, often considered as the main factors leading to geographic variation in reproductive aspects (Henmi, 1993;Lardies & Castilla, 2001;Terossi et al, 2010). However, even though presenting similar fecundity per brood, brood frequency of populations in different geographical areas may vary (Richard G. Hartnoll, personal conamunication).…”
Section: Cwmentioning
confidence: 93%